The Effect of the Substitution of Banana Blossom Flour (Musa paradisiaca) and Mung Bean (Vigna radiata) on Proteins, Fiber, and Steamed Brownies Sensory - Intan Septia Rahayu; Bernatal Saragih; Rieska Indah Mulyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
In an effort to prevent the occurrence of protein and fiber energy deficiencies, researchers conducted research, namely the use of local materials to be made as brownies products so that they can become products that can be consumed by the community. These brownies are made from banana bloaaom flour and mung beans as raw materials. This research was conducted with a Completely Randomized Design (CRD) with 3 repetitions consisting of 1 factor, namely the proportion of brownie formulations substituted with banana heart flour and green beans for the total subject to test acceptability with the hedonic test method and hedonic quality as many as 25 moderately trained panelists. Proximate nutritional value test. The analysis used the one-way Anova test. The results of the research on proximate levels of the product showed that the nutritional value based on the percentage treatment of banana heart flour and mung bean (15:35%) was the most preferred to get 370.0 kcal of energy nutrition, 9.25 g of fiber, 31.4 g of water, 31.4 g of water content. ash 2.21 g, fat 20.9 g, protein 5.19 g, and carbohydrates 40.